2020
DOI: 10.11591/ijece.v10i6.pp6412-6422
|View full text |Cite
|
Sign up to set email alerts
|

The effect of technology-organization-environment on adoption decision of big data technology in Thailand

Abstract: Big data technology (BDT) is being actively adopted by world-leading organizations due to its expected benefits. However, most of the organizations in Thailand are still in the decision or planning stage to adopt BDT. Many challenges exist in encouraging the BDT diffusion in businesses. Thus, this study develops a research model that investigates the determinants of BDT adoption in the Thai context based on the technology-organization-environment (TOE) framework and diffusion of innovation (DOI) theory. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Structural equation model (SEM) was used to test the hypothesis. The results show that the statistical fitting between the research model and empirical data is: normalized chi-square= 1.651, GFI = 0.895, AFGI = 0.863, NFI = 0.930, TLI = 0.964, CFI = 0.971, SRMR = 0.0392, RMSEA = 0.046 [1]. GhallabH proposed a big data technology, a new model NRDD-DBSCAN on account of DBSCAN algorithm, which uses elastic distributed data sets (RDD) to detect anomalies affecting the data quality of iot technologies.…”
Section: Introductionmentioning
confidence: 90%
“…Structural equation model (SEM) was used to test the hypothesis. The results show that the statistical fitting between the research model and empirical data is: normalized chi-square= 1.651, GFI = 0.895, AFGI = 0.863, NFI = 0.930, TLI = 0.964, CFI = 0.971, SRMR = 0.0392, RMSEA = 0.046 [1]. GhallabH proposed a big data technology, a new model NRDD-DBSCAN on account of DBSCAN algorithm, which uses elastic distributed data sets (RDD) to detect anomalies affecting the data quality of iot technologies.…”
Section: Introductionmentioning
confidence: 90%
“…Consistently, technological readiness in the present work refers to a bank's readiness and capacity to accept and use cutting-edge technology to improve operations, enhance client experiences and maintain competitiveness in the digital era. Related research has revealed a link between BDA and technological readiness (Aziz, Long, & Wan Hussain, 2023;Maroufkhani, Iranmanesh, & Ghobakhloo, 2023;Saetang et al, 2020). Similarly, future trends in BDA technology readiness are highlighted by recent studies (Huang, Yao, Krisp, & Jiang, 2021), including the incorporation of artificial intelligence (AI), the growing use of cloud-based solutions and the introduction of blockchain for data security.…”
Section: Technology Readinessmentioning
confidence: 98%
“…Numerous studies have supported the ability of TOE in explaining various technologies' adoption in an organizational setting (El-Haddadeh, Osmani, Hindi, & Fadlalla, 2021;Gupta, Drave, Dwivedi, Baabdullah, & Ismagilova, 2020;Oliveira, Martins, Sarker, Thomas, & Popovi_c, 2019). The fundamental advantage of TOE is that it considers internal and external aspects in a single model, which sets it apart from other theories that explain technology adoption, such as institutional theory, knowledge-based view and technology structuration theory (Saetang, Tangwannawit, & Jensuttiwetchakul, 2020). Similarly, Awa, Ukoha, and Emecheta (2016) explained that due to the combinations of factors considered for adoption, TOE provides more holist insight on technological adoption that other theories which considered attitudinal factors only.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Teori DOI diusulkan oleh Rogers pada tahun 1962 dan dikembangkan lebih lanjut. Adopsi inovasi adalah, proses di mana suatu inovasi dikomunikasikan melalui saluran tertentu dalam jangka waktu tertentu dalam sebuah sistem sosial (Rogers, 2003).…”
Section: Tinjauan Pustakaunclassified
“…Inovasi dan karakteristik organisasi keduanya berkontribusi pada adopsi teknologi baru (Sun et al, 2020). Lima faktor penentu penting yang dapat memengaruhi tingkat adopsi dalan inovasi, yaitu relative advantage, complexity, complexity, trialability, dan observability (Rogers, 2003). Jadi dapat disimpulkan bahwa model DOI tersebut berfokus pada peran atribut teknologi yang penting untuk adposi TI dalam organisasi.…”
Section: Tinjauan Pustakaunclassified